Outcomes of Post‐Acute Care in Home Health Versus a Skilled Nursing Facility in Medicare Beneficiaries with Dementia. (15th September 2021) - Burke, Robert; Xu, Yao; Ritter, Ashley Z.; Werner, Rachel M.
Abstract : Research Objective: To compare the outcomes of post‐acute care between home health (HH) and skilled nursing facilities (SNFs) following hospitalization among Medicare beneficiaries with dementia. Despite the fact that both post‐acute care use and dementia are highly prevalent in the Medicare population, very few studies have compared the outcomes of different post‐acute care settings for patients with dementia, leaving patients, caregivers, and clinicians uncertain how to make optimal decisions around hospital discharge. Study Design: Retrospective analysis of secondary data using an instrumental variable design to compare outcomes of HH versus SNF following an acute hospitalization. We used a 100% sample of Medicare inpatient, outpatient, and post‐acute care claims and assessment data from January 1, 2015 to December 31, 2016 and used differential distance between home health and SNF as the instrumental variable to account for nonrandom allocation of patients (F‐statistic: 26.5). Outcomes included unplanned 30‐day readmission, 30‐ and 100‐day mortality, and a composite measure of readmission and mortality to address competing risks. Our analysis adjusted for beneficiary characteristics and year of analysis, included fixed effects for hospital and year, and adjusted for clustering at the hospital level. Population Studied: We used MedPAR to identify hospitalizations and Minimum Data Set and Outcome and Assessment Information Set assessments to identify SNF and HH stays following hospital discharge. We excluded beneficiaries younger than age 65, admitted to the hospital from a nursing home, or were enrolled in hospice. We identified dementia using validated diagnostic codes with a three‐year look‐back. We also measured demographics, comorbidities, characteristics of the index hospital stay, prior health care utilization, and both cognitive and physical function on admission to post‐acute care. Principal Findings: Our sample included 1, 369, 192 beneficiaries with a diagnosis of dementia; 404, 539 (29.5%) received HH, while 964, 653 (70.5%) went to SNF. The cohort was older (mean age 83), approximately 70% were cognitively impaired on SNF admission, and only 30.4% of patients were independent in Activities of Daily Living. Overall, 16.1% were readmitted to the hospital and 5.9% died within 30 days, while 19.5% died within 100 days of hospital discharge. In the instrumental variable analysis, there were no differences in any outcome between the two post‐acute care settings. These findings were similar when the analysis was stratified by degree of cognitive impairment. Conclusions: In a sample of more than 1.6 million Medicare beneficiaries discharged to post‐acute care following hospitalization, use of home health services and SNF were equivalent in terms of unplanned readmissions and 30‐ and 100‐day mortality. These are important findings given more than 7 in 10 Medicare beneficiaries with dementia are currently discharged to SNF for post‐acute care at much higher cost than HH, and the prevalence of both dementia and post‐acute care use are increasing in the United States. Implications for Policy or Practice: Our findings suggest HH may provide similar outcomes at lower cost following hospitalization for Medicare beneficiaries with a diagnosis of dementia, and that home‐based models of care may provide increased post‐acute care value. Primary Funding Source: University of Pennsylvania Institute on Aging.